Kepraktisan dan Keefektifan Penggunaan E-LKPD Konteks Sosial Budaya Berbantuan Workbook GeoGebra terhadap Kemampuan Numerasi Peserta Didik pada Materi Limas - Sidik, Zafar Muhamad; Susanto, Susanto; Suwito, Abi; Setiawan, Toto Bara; Safrida, Lela Nur (Jurnal Tadris Matematika, 2023)
Numeracy is a person's ability to implement mathematics in the home, work and community environments. This research aims to measure the practicality and effectiveness of using E-LKPD in a socio-cultural context assisted by GeoGebra workbooks in improving students' numeracy skills in pyramid material. The type of research used was a quasi-experiment (Quasi-experiment) with research subjects 21 class VIII students at SMPN 1 Kalisat Jember. The practicality of E-LKPD is assessed from the results of student response questionnaires, while the effectiveness of E-LKPD is assessed from the results of students' numeracy ability tests. The use of E-LKPD is said to be practical if the average percentage of students' questionnaire responses is at least in the practical category, and effective if students' numeracy skills are at least in the medium category. Based on the practicality analysis, the results of the student response questionnaire regarding the use of E-LKPD obtained a percentage of 81.67% or were in the practical category. In addition, the use of E-LKPD shows an increase in students' numeracy skills on all numeracy indicators. This can be seen based on the results of the numeracy ability test which obtained an N-Gain score of 0.51 or at a medium effectiveness level. Therefore, the use of E-LKPD in a socio-cultural context with the help of GeoGebra workbooks is practical and effective for improving students' numeracy skills, especially in learning surface area and volume of pyramids.